Meningkatkan Hasil Belajar Siswa Dalam Memahami Materi Keberagaman Masyarakat Indonesia (Bingkai Bhineka Tunggal Ika) Pada Mata Pelajaran Pendidikan Kewarganegaraan (Pkn) dengan Menggunakan Model Pembelajaran Interaktif Pada Siswa Kelas IV SDN Kadudampit - Rianda Nurarianti; Rifki Arif Nugraha; Dewi, Dewi; Ajeng Muliasari (KRAKATAU (Indonesian of Multidisciplinary Journals), 2023)
ABSTRACT This study aims to improve student learning outcomes in the Citizenship Education (PKN) subject by using an interactive learning model for fourth grade students at SDN Kadudampit 3, Saketi District, Banten Province. This research is a class action research model by Kemmis and Mc Taggart. The research was carried out in an odd semester or at the beginning of the 2023/2024 school year in three cycles, each cycle consisting of one meeting. The subjects of this study were fourth grade students at SDN Kadudampit 3, Saketi District, Banten Province, totaling 36 students. Data collection techniques used are tests, observations, and documentation. While the data collection instrument used test questions, observation sheets and documents. Data analysis techniques were carried out qualitatively and quantitatively. The results showed that there was an increase in student learning outcomes on civics education material in class IV SDN Kadudampit 3 Saketi District, Banten Province. Learning outcomes in pre-cycle, the class average is 55.33 for completeness is 4 students or 11% and there are 32 students or 89% incomplete. .66, for completeness is 22 students or 61%, and those who have not completed are 14 students or 39%, which means there is an increase in the average pre-cycle to cycle I of 18.5, while the results of cycle II have increased again, i.e. the class average increased to 80.47 with completeness reaching 31 students or 86.87% and those who had not completed were 5 students or 14%, thus there was an average increase from cycle I to cycle II of 6.98. Whereas for cycle III it increased again so that the average value reached 85.44, with 33 students or 92% completeness and 3 students or 8% who had not completed, thus there was an average increase from cycle II to cycle III of 5 In addition, the activeness of students in following the lessons also increased, this was indicated by the increased activity of students in asking questions, answering questions, and expressing opinions. This illustrates that learning with an interactive learning model has been going well and can support an increase in student learning outcomes on the subject of the diversity of Indonesian students. Therefore it is suggested that teachers in teaching subject matter should prioritize interactive learning models. Keywords: Learning Outcomes, Citizenship Education, Interactive Learning